Strategic business transformation synergy, corporate sustainability in the energy sector by systematic literature review - Situmorang, Patar; Purba, John Tampil; Harianja, Evo Sampetua (International Journal of Innovative Research and Scientific Studies, 2025)
This systematic literature review (SLR) aims to identify the key determinants influencing corporate sustainability in the energy sector. The review synthesizes findings from 54 peer-reviewed articles sourced from the Scopus database. The study adopts the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, ensuring a rigorous methodological process through clearly defined inclusion criteria, comprehensive database searches, and systematic screening and selection of relevant studies. The review reveals that corporate sustainability in the energy sector is driven by both external and internal factors. Key external determinants include climate change awareness, regulatory compliance, stakeholder pressure, sustainability reporting quality, risk perception, market and competition dynamics, and government support. Internal factors consist of technology adoption, strong leadership, top management support, business transformation, firm size, human resource management, organizational culture, service delivery, service innovation capability, and dynamic capability. This review contributes to the understanding of corporate sustainability in the energy sector by offering practical implications for industry stakeholders and policymakers, supporting the development of sustainable practices and long-term sustainability strategies.